The Effect of Word of Mouth on Tourists' Visiting Decisions to the Culinary Tourism Destination of Tanjung Pakis Beach, Karawang Regency - Putri, Nadhia; Turgarini, Dewi; Pratami Putri, Dias (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2025)
The problem studied in this study is the influence of word of mouth on tourists' decision to visit the culinary tourism destination of Tanjung Pakis Beach, Karawang Regency. The type of research used in this study is quantitative research. Data collection techniques using observation and questionnaires. This study used a sample of 100 (one hundred) respondents. The instrument testing technique in this study was the validity and reliability test, while the data analysis technique used the classical assumption test, multiple linear regression analysis, and hypothesis analysis using the SPSS version 26 application to process the data. The results showed that there was a significant influence of both variables (word of mouth and culinary tourism) on the decision to visit the Tanjung Pakis Beach tourist attraction in Karawang, West Java. So the hypothesis that states that word of mouth and culinary tourism have a positive effect simultaneously on the decision to visit the Tanjung Pakis Beach tourist attraction in Karawang, West Java is proven true.